SISTEM REKOMENDASI TRAVEL UMRAH DI JAKARTA BERBASIS WEB DENGAN METODE ANALYTICAL HIERARCHY PROCESS DAN SIMPLE ADDITIVE WEIGHTING - Diri Anindyah Qonita Dwi Putri; Bagus Mulyawan; Tri Sutrisno (Fakultas Teknologi Informasi Universitas Tarumanagara, 2019)
The Umrah travel recommendation system is an application made using the Analytical Hierarchy Process (AHP) method and the Simple Additive Weighting (SAW) method. This application will provide recommendations for Umrah travel, first with the AHP method. The AHP method performs pairwise comparisons using the paired comparison scale determined by Saaty, which will then produce priority weight per criterion to be used in the process of calculating preference values in the SAW method ranking, the results of priority weights obtained are price, down-payment, distance, facilities, the number of pilgrims and travel packages is 0.304, 0.304, 0.202, 0.087, 0.072, 0.032. In the SAW method was chosen in determining the ranking of Umrah travel data with predetermined criteria. Tests were carried out using 50 Umrah travel data in Jakarta obtained online. The results can be concluded that Al-Razafa is the first choice with SAW 0.931.